Feed Type and Level of Viterna on Body Weight, Percentage of Carcass, Non-Carcass and Abdominal Fat of Broiler Chickens - Dappa, Enjelina; Mulyantini, N. G. A; Theedens, Jonas F; Telupere, Frangky M. S (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
This study aims to examine the effects of different types of feed and level of viterna on the final body weight, carcass percentage, non-carcass, and abdominal fat of broiler chickens. The method used was a 2x4 factorial Completely Randomized Design. The first factor was 2 types of commercial feeds (J1=A and J2=B). The second factor was 4 levels viterna (P0=0cc; P1=1.5cc; P2=3cc; P3=4.5cc/l drinking water). There were 8 treatment combinations with 4 replications, and each replicate consist of 4 chickens, a total of 128 broilers was used. The treatment combinations were as follows: J1P0=feed A without viterna in drinking water, J1P1= feed A+1.5cc viterna/l water, J1P2 = feed A+ 3cc viterna/l water, J1P3= feed A + 4.5cc viterna/l water, J2P0 = feed B without viterna in drinking water, J2P1= feed B + 1.5cc viterna/l water, J2P2=feed B + 3cc viterna/l water, J2P3= feed B + 4.5cc viterna/l water. The measured variables were final body weight, carcass percentage, non-carcass, and abdominal fat. Data were analyzed using a variance test at a significance level of 5%, treatments that were significant (P≤0.05) followed by the Duncan Multiple Range Test. The results showed that there was no interaction (P>0.05) between feed type and viterna level on all parameters. In conclusion, differences in the type of feed, and viterna level, also interaction between the two factors did not make a difference to the final weight, percentage of carcass, non-carcass, and abdominal fat of broiler chickens.